Coping Mechanism of Kindergarten Parents in a Modular Learning Education for the School Year 2021-2022 - Solomo, Jovi; Bitara, Amando; Valencia, Marlene; Purigay, Gerald; Regullano, Maribel; Cruzana, Joseph; Abordo, Helen (IJBLE Scientific Publications Community Inc., 2023)
Parents, teachers, and students were equally affected by the widespread prevalence of COVID-19. Parental involvement in the education of students begins at home, providing a safe and healthy environment, appropriate learning experiences, support, and a positive attitude about school (Durisic & Bunijevac 2017). A descriptive qualitative study was planned to explore the experiences of parents coping mechanisms. The purposive sampling technique was used for data collection. Data were collected from 35 kindergarten parents; through an open-ended question. Three major themes emerged after the data analysis: the teaching experience of a kindergarten parent, the coping mechanism, and the most suitable approach used. It was analyzed that their parent-children's relationships positively influenced the coping-up mechanism. The child's behavior, what interests them most, and not overworking them with the modules were also considered. It is recommended that in-depth orientation about the learning mechanism be included during Parent-Teacher Conference (PTC).